Influence of tumor characteristics (Lesion type, stage, grade) on postoperative outcomes following holmium laser resection – A cross-sectional observational study. - Siddhartha, Thota; Jumde, Suvit (Student's Journal of Health Research Africa, 2025)
Background Transurethral resection of the bladder tumor (TURBT) is the usual treatment for these tumors, which is followed by further intravesical chemotherapy or immunotherapy. But problems, including bleeding, obturator nerve reflex (ONR), and bladder perforation, are linked to TURBT. Objectives- The study primarily evaluated the impact of tumor attributes, including lesion kind, stage, and grade, on the results of surgery after Holmium laser resection. Materials and methods It was a cross-sectional, observational study. The study was carried out in the Department of Urology, Mahatma Gandhi Medical College and Research Institute, Puducherry, India. The study was conducted for one and a half years, that is, from December 2021 to Jun 2023. In all, 24 patients were enrolled. Results Seven patients (29.2%) had numerous lesions, compared to the majority of 17 patients (70.8%) who had single lesions. Ten (41.7%) patients had high-grade cancers, whereas 14 (58.3%) patients had low-grade tumors. With a p-value of 0.017, patients with many lesions needed many more analgesic vials after surgery. Catheterization time, hospital stay, analgesic use, and operation time did not significantly change between the T1 and Ta stages. Conclusion This study demonstrates that among the various tumor characteristics evaluated, only the presence of multiple lesions significantly influenced postoperative outcomes, specifically resulting in increased analgesic requirements. Recommendations Larger, multicenter studies are recommended to validate these findings and assess long-term outcomes.